KERUKUNAN UMAT BERAGAMA DARI TINJAUAN HADIS (PROBLEMATIKA EPISTEMOLOGIS) - Winda Sari; Yuzaidi Yuzaidi (UIN Sumatera Utara Medan, 2022)
The study of religious harmony is important, because religious sentiments often lead to conflict of tension. Not only in Indonesia, but also in other parts of the world, although social, political, economic factors are quite coloring, but the role of religion can not be denied in social conflict. This is meanly related to the lack of tolerance towards other faiths. Among the way to create religious harmony is to examine the framework of islamic epistemology analysis on the basis of religious harmony. Islamic epistemology believes in the source of the truth of revelation, reasion, empirical, and intuition. The methods and tools used in the search of truth are the guidence of revelation, reasion, empirical, and intuition. The Theological basis examined in this study is derived from The Hadiths of The Prophet Muhammad that are relevant with religious harmony. This study is included in the literature study category with primary data taken from the books of hadiths and supported by secondary data from various books that examine the religious harmony. Islamic epistemology is used as an analytical blade of foundation for exploring sourches of truth which are related to the foundations of religious harmony in the hadiths of the Prophet Muhammad which later expected to grow awareness to respect each other. This step is expected to be one of intersections that bridges the realization of religious harmony, especially in Indonnesia.